Model Pembelajaran Berbasis Pengalaman untuk Penguatan Karakter Anti-Korupsi Mahasiswa Vokasi - Hasan,, Riza; Fitrayansyah, Fitrayansyah (VOCATECH: Vocational Education and Technology Journal, 2025)
Abstract[1] Vocational higher education in Indonesia bears a strategic responsibility to produce graduates with technical competence and integrity. This research aims to develop an experiential learning model in citizenship education to strengthen anti-corruption character among students at the State Community Academy of West Aceh and to analyze its implementation challenges. A qualitative approach with case study design was applied through triangulation of data collection techniques including in-depth interviews, participatory observation, documentation study, and focused group discussions with one lecturer, twenty students, and three stakeholders. The findings reveal that the learning model integrating four theoretical frameworks (experiential learning, moral character education, situational learning, and local wisdom) effectively strengthened students' anti-corruption character. The model was implemented through three systematic phases (awareness, internalization, application) which resulted in transformation across four character dimensions: cognitive, affective, behavioral, and spiritual-cultural. The integration of Acehnese local wisdom values (trustworthiness, justice, honesty, purity, patience) provided cultural resonance that strengthened the internalization of anti-corruption values. Implementation challenges encompassed structural-institutional, pedagogical, and contextual aspects which were addressed through lecturer competency development strategies, learning time optimization, and contextualization of simulations according to study programs.Keywords:[2] experiential learning; local wisdom; anti-corruption education; vocational education; experience-based learning  Abstrak[3] .Pendidikan tinggi vokasi di Indonesia memiliki tanggung jawab strategis dalam menghasilkan lulusan dengan kompetensi teknis dan karakter berintegritas. Penelitian ini bertujuan mengembangkan model pembelajaran berbasis pengalaman dalam pendidikan kewarganegaraan untuk memperkuat karakter anti-korupsi mahasiswa di Akademi Komunitas Negeri Aceh Barat serta menganalisis tantangan implementasinya. Pendekatan kualitatif dengan desain studi kasus diterapkan melalui triangulasi teknik pengumpulan data yang meliputi wawancara mendalam, observasi partisipatif, studi dokumentasi, dan diskusi kelompok terfokus terhadap satu dosen pengampu, dua puluh mahasiswa, dan tiga pemangku kepentingan. Hasil penelitian mengungkapkan bahwa model pembelajaran yang mengintegrasikan empat kerangka teoretis (experiential learning, pendidikan karakter moral, pembelajaran situasional, dan kearifan lokal) terbukti efektif memperkuat karakter anti-korupsi mahasiswa. Implementasi model dilakukan melalui tiga fase sistematis (penyadaran, penghayatan, penerapan) yang menghasilkan transformasi pada empat dimensi karakter: kognitif, afektif, behavioral, dan spiritual-kultural. Integrasi nilai-nilai kearifan lokal Aceh (amanah, adil, jujur, bersih, sabara) memberikan resonansi kultural yang memperkuat internalisasi nilai anti-korupsi. Tantangan implementasi mencakup aspek struktural-institusional, pedagogis, dan kontekstual yang dapat diatasi melalui strategi pengembangan kompetensi dosen, optimalisasi waktu pembelajaran, dan kontekstualisasi simulasi sesuai program studi. Kata Kunci: [4]             experiential learning; kearifan lokal; pendidikan anti-korupsi; pendidikan vokasi; pembelajaran berbasis pengalaman